PENGARUH DIFERENSIASI PRODUK TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN (Survei pada Pelanggan “Cake in Jar” Cafe Bunchbead Kota Malang) - Thariz Baharmal Dejawata (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
The population increase and growth of lifestyle has impacted on businessman to take opportunities in the culinary business. The objectives of this research is to identify and explain the effect of product differentiation on Customer Satisfaction and Customer Loyalty. A survey was conducted on the customer of